2012
DOI: 10.1016/j.ajpath.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

ProxTom Lymphatic Vessel Reporter Mice Reveal Prox1 Expression in the Adrenal Medulla, Megakaryocytes, and Platelets

Abstract: Lymphatic vessels (LVs) are important structures for antigen presentation, for lipid metabolism, and as conduits for tumor metastases, but they have been difficult to visualize in vivo. Prox1 is a transcription factor that is necessary for lymphangiogenesis in ontogeny and the maintenance of LVs. To visualize LVs in the lymph node of a living mouse in real time, we made the ProxTom transgenic mouse in a C57BL/6 background using red fluorescent LVs that are suitable for in vivo imaging. The ProxTom transgene co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(78 citation statements)
references
References 43 publications
3
75
0
Order By: Relevance
“…Gene-targeted mice expressing a Cre-recombinase or a fluorophore under an LEC-specific promoter have recently been generated, [32][33][34][35][36] but only 2 IVM studies performed in such mice have been reported so far. 35,36 Therefore, to date, LVs have mainly been visualized in IVM by in vivo labeling with intracutaneously injected fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene-targeted mice expressing a Cre-recombinase or a fluorophore under an LEC-specific promoter have recently been generated, [32][33][34][35][36] but only 2 IVM studies performed in such mice have been reported so far. 35,36 Therefore, to date, LVs have mainly been visualized in IVM by in vivo labeling with intracutaneously injected fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 Therefore, to date, LVs have mainly been visualized in IVM by in vivo labeling with intracutaneously injected fluorescent antibodies. 4,37,38 However, antibody labeling is considered less optimal for IVM than endogenous expression of fluorophores; it is typically restricted to the injection site and downstream regions and could interfere with leukocyte-endothelium interactions or lead to unwanted immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…After staining, eyes were fixed overnight in 10% formalin before paraffin embedding and sectioning using standard methods. Prox1-tdTomato [Tg(Prox1-tdTomato)] mice were a gift from Guillermo Oliver (Northwestern University Feinberg School of Medicine, Chicago, Illinois, USA) and were genotyped as previously described (40). Adult eyes were used for whole-mount immunostaining as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of lymphocyte, DC, and antigen-trafficking patterns in TLOs in real time in vivo is now possible with the use of mice that express fluorescent markers for HEVs (80) and LVs (79,81). Although the technique of in vivo imaging is well established for analysis of trafficking in LNs (82), addressing this issue in TLOs is a greater challenge.…”
Section: Future Research Directionsmentioning
confidence: 99%